ANALISIS PERGESERAN DINDING CANDI BOROBUDUR MENGGUNAKAN ROBOTIC TOTAL STATION (RTS) - Calvin Wijaya; Rizal Mubarok; Raniah Salsabila; Joni Setiyawan (Balai Konservasi Borobudur Magelang, 2022)
Borobudur temple is one of the world's cultural heritages which located in Magelang, Central Java. This largest temple in Indonesia has historical and cultural values that are very valuable, so it is important to be maintained and preserved. One way of preservation that can be done is to monitor the structure of temple walls. This purpose of this monitoring is to observe if there is a shift or movement in the earth’s plates and non-natural factors. The development of survey technology with Robotic Total Station (RTS) will make easier to monitor the structures. The monitoring method is carried out used the principle of geodetic measurement to measure 60 monitoring prisms on all sides of the temple in three cycles. The results of the monitoringshowedthat magnitude of the shift in this temple walls was small, which was under than 1 mm on all sides, so that it can be categorized as relatively stable temple wall.